E-module of Pancasila Education Subject Based on Pancasila Student Profile for Students in Second Grade of Elementary School - Rianti, Ni Luh; Wulandari, I Gusti Agung Ayu; Wiyasa, I Komang Ngurah (Universitas Pendidikan Ganesha, 2024)
Lack of resources such as adequate textbooks, is a challenge for teachers in implementing innovative learning methods. This study aims to analyze the feasibility and determine the effectiveness of the Pancasila Education E-module based on the Pancasila Student Profile. This study is a development research with the Dick and Carey development model. This study involved 1 subject expert, 1 instructional design expert, 1 learning media expert, 3 students for individual trials, and 9 students for small group trials. Data collection methods used include multiple-choice objective tests and questionnaires. The data analysis techniques applied are quantitative and qualitative methods. The results of the study showed (1) the feasibility of the E-module media showed the results of the subject matter expert test of 98.33%, the language expert test of 96.66%, the learning media expert test of 96.66%, the instructional design expert test of 97.22%, the individual trial of 98.33%, and the small group trial of 98.61%. (2) The effectiveness of the Pancasila Education E-module media based on the t-test results obtained a significant value of 0.000 with a decision of ≤ 0.05, then H0 is rejected and H1 is accepted. Thus, the results of this study indicate that the Pancasila Education E-module media is effective for use on grade II elementary school students.